METODE ISOLASI PYRICULARIA ORYZAE PENYEBAB PENYAKIT BLAS PADI - Wicaksono, Danar; Wibowo, Arif; Widiastuti, Ani (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Isolation method of Pyricularia oryzae the causal agent of rice blast disease. Rice blast disease is a disease that reduces rice productivity and threatens global food reserves. The study of diversity and distribution of race fungal causing rice blast disease required a fungal isolates collection from different places and times. One of the challenges in collecting these fungi is the difficulty of isolation process. The purpose of this research was to study the proper isolation method of rice blast pathogen. The most appropriate isolation method of Pyricularia oryzae was to moisten the infected panicle, place on moist filter paper in a petri dish, and incubate plate for 2 days at room temperature under fluorescent lamp. Afterward, conidium was picked using sterile needle and transfered to potato dextrose agar without lactic acid.